Analyzing the Impact of Working Capital Management on Profitability: A Study on Dse Listed Cement Companies in Bangladesh (Global Journal of Management and Business Research, 2018)
The study is an analysis on the impact of working capital management on profitability of cement companies in Bangladesh. The study comprises all the 7 cement companies that are listed on the Dhaka Stock Exchange (DSE). Gross Operating Profit has been used as proxy for profitability and cash conversion cycle and its components (accounts receivable period, inventory conversion period and payables deferral period) have been used as proxy for working capital. The study used panel data regression technique and data were collected from secondary sources for the period 2007-2015. Results show that cash conversion cycle, accounts receivable period and inventory conversion period have significant negative impact on profitability whereas payables deferral period has significant positive impact on profitability for the sampled companies.
Keywords: working capital management; working capital; profitability; bangladesh